28. INTERGLACIAL POLLEN RECORDS FROM SCHÖNINGEN, NORTH GERMANY - Urban B. (My University, 2007)
The Pleistocene sequence of the Schöningen lignite mine contains a number of interglacial and interstadial limnic and peat deposits, travertine tuff, soils, tills and fluvioglacial as well as loess deposits. There is evidence of four interglacials younger than the Elsterian glaciation and preceding the Holocene. The complex Pleistocene sequence contains six major cycles. The sequence begins with Late Elsterian glacial and interstadial deposits preceding the Holsteinian, followed by the Reinsdorf and Schöningen interglacials, which represent the pre-Drenthe (Early Saalian Stadial) period. A pedocomplex developed in alluvial loess, younger than the Drenthe Stadial of the Saalian glaciation, is succeeded by a sequence of soft travertine and peat representing Eemian marine isotope stage 5e (MIS 5e) and MIS substages 5d, 5c. Channel sediments provide evidence of the Weichselian late glacial and the Holocene. The Schöningen pollen record of MIS 5 and tentative correlatives of MIS 7, 9 and 11 as well as temperate interstadials of Late Elsterian and (intra) Saalian (s.l.) age are discussed and compared with other pollen records of North Germany, Western and Central Europe. Detailed pollen evidence for the Reinsdorf sequence, which is significant for its Lower Palaeolithic sites, including stadials and interstadials, is a major focus. © 2007 Elsevier B.V. All rights reserved.
Keywords: 230TH/234U DATING; INTERGLACIALS; PALAEOBOTANY; PALAEOCLIMATE; PLEISTOCENE; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная::Плейстоцен